Chondral tissue engineering of the reumatoid knee with collagen matrix autologous chondrocytes implant - Leigheb, Massimiliano; Bosetti, Michela; De Consoli, Antonio; Borrone, Alessia; Cannas, Mario; Grassi, Federico (Acta Biomedica Atenei Parmensis, 2017)
Articular cartilage repair is still a challenge. To date evidence is insufficient to support a treatment over the others. Inflammatory conditions in the joint hamper the application of tissue engineering during chronic joint diseases. Most of the Matrix Autologous Chondrocyte Implantation (MACI) cases reported in literature do not deal with rheumatoid knees and do not have a long clinical-histologic follow-up. We report about a 46-year old woman who suffered of a painful focal Outerbridge 4th degree chondral lesion in the medial femoral condyle of her left rheumatoid knee. The tissue defect was filled by a Cartilage Regeneration System (CaReS®) based on a type I collagen matrix seeded by autologous in vitro expanded chondrocytes. The patient was followed up to ten years clinically and by MRI, and finally treated with a Total Knee Replacement for the increasing arthritis. Histologically, the explanted MACI tissue showed an increased cellularity with an extracellular matrix rich of collagen and glycosaminoglicanes even though the overall architecture was different from the normal cartilage pattern. The case reported suggests that the main goal of treatment for chondropathy is the long lasting control of symptoms, while permanent restoration of normal anatomy is still impossible. Mesenchymal stem cells, that develop into joint tissues, show immunosuppressive and anti-inflammatory qualities, in vitro and in vivo, indicating a potential role for tissue engineering approaches in the treatment of rheumatic diseases.